2008
DOI: 10.1088/0741-3335/50/12/124012
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and simulation of edge turbulence and filaments in MAST

Abstract: Experimental and simulation results on filamentary structures observed in the Mega-Amp Spherical Tokamak (MAST) are presented and discussed. Fast camera data have been used to determine the mode number, toroidal and radial sizes and velocities of the filaments observed in L-mode, inter-edge localized mode (ELM) periods and ELMs which are summarized. Automated methods are applied to the analysis of L-mode image data in order to measure dependence with plasma parameters. This indicates that the mode number of L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 24 publications
4
79
0
Order By: Relevance
“…Interestingly, the filaments propagate in the radial direction with a relatively constant velocity, a result consistent with previous results in MAST [10,11,35] and in literature [27] (although this might not be a universal feature, see [7,[36][37][38]). Filament 1 and 2 move with average radial velocities of around 1.5 km s −1 and 0.6 km s −1 , respectively, in agreement with previous measurements in similar conditions [26,35]. The half width (i.e.…”
Section: Filaments Dynamics and Geometrysupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the filaments propagate in the radial direction with a relatively constant velocity, a result consistent with previous results in MAST [10,11,35] and in literature [27] (although this might not be a universal feature, see [7,[36][37][38]). Filament 1 and 2 move with average radial velocities of around 1.5 km s −1 and 0.6 km s −1 , respectively, in agreement with previous measurements in similar conditions [26,35]. The half width (i.e.…”
Section: Filaments Dynamics and Geometrysupporting
confidence: 90%
“…The camera resulution was such that sub centimeter filaments could be resolved, as tested using syntetic signals. In order to enhance the filamentary structures we used a background subtraction technique [26] which calculates in each pixel the minimum light intensity over 16 frames (current frame plus 15 others) and subtracts this from the frame of interest. It is observed that the background emission peaks in the region of the separatrix, where the neutral ionisation is maximum.…”
Section: Diagnostics and Analysis Techniquementioning
confidence: 99%
“…8 left). The characteristics of these filaments as deduced from the visible imaging are listed in Table 1 [34]. This comparison suggests that the sporadic inter-ELM filaments are more closely related to L- mode filaments than to ELM filaments (e.g.…”
Section: Sol Modelling and Edge Filamentsmentioning
confidence: 94%
“…93,100 3D simulations have been used to make comparisons of blob size (or poloidal correlation length), 74,88 parallel filament structure, 74,88,140 and blob velocity. 74,91 Typically, the agreement was reasonable (factor of 2) for some quantities but poor for others. In some cases, it was impossible to compare the same quantities in both simulation and experiment; in other papers, the simulation parameters were not varied over a large enough range to optimize the comparison.…”
Section: -39mentioning
confidence: 99%